Climate Change: Understanding it Links Directly to Achieving National Space Policy Goals While Being Useful at Tactical and Strategic Levels - Kimball, Mindy (2011)
The 2010 National Security Strategy states that "the danger from climate change is real, urgent and severe." Several recently updated Army and Joint publications list climate change among the most prominent challenges facing our national security. Army Field Manual 3-0 lists climate change in paragraph 1-1 and 1-7 as an important trend that will affect ground force operations. Joint Publication 3-0 tasks regional commanders with the responsibility to "detect, deter, or when directed, defeat threats to the homeland before they arise [in forward regions outside U.S. territories]." The 2010 Joint Operation Environment lists climate change as one of ten trends influencing the world's security, and GEN J.N. Mattis describes in the Foreword that these trends "remind us we must stay alert to what is changing in the world if we intend to create a military as relevant and capable as we possess today." But why should a Space Professional specifically understand climate change and its implications? Besides the basic doctrine and threat to national security, the June 2010 National Space Policy lists monitoring climate and global change as part of the five goals: "Improve space-based earth and solar observation." Competent space professionals must identify a subject that touches space and do all they can to learn about that subject. They must then inform commanders and provide them with expertise, increased capability and context. Eight distinct reasons for understanding climate change are outlined below, yet this list is surely not complete. Published in the Army Space Journal, p52-55, Fall 2010-Winter 2011.